(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
Lower (C2-C4) olefins, the basic building blocks of chemicals, can be directly synthesized from synthesis gas (H2/CO) from various non-petroleum carbon resources, but the selectivity for lower olefins is very high. We report that coupling the methanol synthesis and methanol-to-olefin conversion reactions with a bifunctional catalyst can realize the direct conversion of syngas to lower olefins with very high selectivity. We show that the choice of the two active components and the method of combining the components are crucial for the selectivity of olefins. The binary Zr-Zn oxide itself shows high selectivity for methanol and dimethyl ether even at 673 K, and the reduced acidity SAPO-34 compound provides approximately 70% selectivity for C2-C4 olefins in the conversion of 10% CO. The proximity of the components at the micro and nanoscale contributes to the low selectivity of olefins